USING DIRECTIONAL TRACKING STRATEGY IN IMPROVE STUDENT’S READING COMPREHENSION - A. Muh Suhair; Sujariati; Hambali, Uyunnasirah (FKIP Unismuh Makassar, 2023)
This study sought to determine whether using a directional tracking strategy, which concentrated on level reading comprehension and included literal reading comprehension in terms of the primary idea and supporting notion, improved students' reading comprehension. The study was applicable pre-experimental research using pre- and post-text for one group. The researcher employed the entire sampling approach. 29 students from class XI of IPS Sma Al Jameah Pattuku served as the research sample. In both the pre-test and post-test, the researcher employed reading test practise as an instrument. The research findings indicated that directional tracking strategies can enhance students' comprehension of what they read. It was demonstrated by the fact that the pre-mean test's score, which was 65.36 and was rated as fair, improved by 21.05% to 79.12 and was rated as good. As a result, the student's reading comprehension in terms of the primary idea and supporting idea improved. Literal comprehension is the end result of improvement. The study discovered that (20.34%) had a higher value than (21.77%). This figure indicates that there was an improvement between the student's pre-test and post-test results. The application of the directional tracking strategy to enhance students' reading comprehension in the SMA Eleventh Grade was found to be effective. The Al Jameah Pattuku.